Eskimo women and boy, ca. 1904 - Nowell, Frank H., 1864-1950 (1904)
To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number